Little red riding hood: hello friend (Hello friend India, 2010)
Little Red Riding Hood sets off to visit her grandmother, but a cunning wolf has other plans. The wolf tricks her, and when he reaches the grandmother first, a tense confrontation ensues. With the help of a nearby woodsman, they outsmart the wolf and save the day.